Prosedur Pemeriksaan MRI MRCP Pada Kasus Kolelitiasis - Alan Pratama; I Made Lana Prasetya; Iman Nuriman (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2023)
The purpose of this research is to know the inspection procedureMRCP and the role of giving bitter tea before examination asnegative oral contrast media. This research is a descriptive qualitative with a case study approach. Subjects consisted of 3 patients with clinicalCholelithiasis. Examination using MRI 1.5 Tesla to find out the procedure and the role of giving bitter tea asnegative oral contrast media. From the results obtained according to the theory of using 400 ml of black tea, 300 ml of jasmine tea and 300 ml of black tea with 40 grams of sugar. While in the field using a different type of tea with an amount of 100 ml before the inspection. Checks are carried out usingbody coil patient position iesupine, feet first. Sequence used in inspectionPlain localizer axial, sagittal andcoronal, Calibration, Axial Dual Echo FSPGR BH, Axial 2D Fiesta, Axial T2 FRFSE BH FatSat Asset, Coronal T2 Fiesta andThick slab MRCP Asset. The use of bitter tea before the examination aims to reduce the presence of artefacts in the stomach, small intestine, large intestine and can help the gallbladder organ to tend to enlarge.